The quest for certainty: Introducing zoning into a discretionary system in England and the European experience - Dembski, Sebastian; O'Brien, Phil (Raumforschung und Raumordnung | Spatial Research and Planning, 2023)
The critique of planning and new proposals to reform the English planning system and “rethink planning from first principles” have led to the introduction of rules-based principles into what is regarded as the paradigm of a discretionary planning system, culminating in a recent White Paper, which it is claimed will create a faster and better planning system than the existing discretionary approach. But are these proposals based on an oversimplified understanding of the differences between discretionary and regulatory models, neglecting, for example, the negotiation between stakeholders and the flexibility which also exists in regulatory planning systems? Our contribution will review some of the recent changes of the English planning system and reflect on experiences with zoning in European countries to bust the myth that the planning reform claims to address: the possibility to combine faster decision making with better place making and less interference from local planning authorities.